The long-term outcomes of the Anderson-Kestenbaum procedure - Kuziel, Jeffrey; Pope, Hannah; Kothapalli, Aishwarya J.; Larson, Scott A.; Drack, Arlene; Dumitrescu, Alina V. (Frontiers in Ophthalmology, 2023)
Introduction: Nystagmus is an involuntary, conjugated, rhythmic movement of the eye that can be idiopathic or secondary to ocular or neurologic pathologies. Patients with nystagmus often have a position of gaze in which their symptoms are dampened or absent, referred to as the “null zone.” The Anderson-Kestenbaum procedure is a bilateral recess-resect procedure of the four horizontal rectus muscles which aims to bring the null position into the primary gaze. This study aims to further elucidate long-term outcomes and factors associated with optimal postoperative outcomes. Methods: Patients with a diagnosis of nystagmus and a surgical code for strabismus between June 1990 and August 2017 were considered for inclusion in the study. Patients were included if they had undergone the Anderson-Kestenbaum procedure and had follow-up lasting at least 24 months post-operatively. Data collected included demographic information, characteristics of the nystagmus, underlying etiology of nystagmus, and pre-and post-operative measurements. Results: 25 patients were included. At their last recorded follow-up, 44% of patients achieved an optimal surgical outcome -an abnormal head position of 10 degrees or less. 88% of patients showed an overall improvement in their head posture at the last follow-up. The absence of an abnormal head position at the visit closest to 24 months post-operatively was found to be significantly associated with the lack of a significant head position at the last follow-up visit. Optimal surgical outcomes were not significantly associated with the underlying diagnosis, the direction of the abnormal head position, or the type of nystagmus. Discussion: The relatively long follow-up of this cohort allows this study to further elucidate the long-term outcomes of the Anderson-Kestenbaum procedure. Overall, our results suggest that although improvement in head position post-operatively is likely, it is still expected that many patients will have a residual abnormal head position after the procedure. The results of this study are helpful in counseling patients, especially knowing that if they do not have a significant head position at 24 months follow-up, they are unlikely to develop one. However, due to the small sample size, larger cohorts and more standardized follow-up may provide further insight into the procedure's outcomes.